Oil and the duration of dictatorships - Jesús Crespo Cuaresma; Harald Oberhofer; Paul Raschky (University of Innsbruck, Department of Public Finance, 2008)
This paper develops a simple model that analyses the relationship between a country's oil endowment and the duration of its autocratic leader. The dictator uses the rents from oil extraction for both personal gain and to pay-off potential opposition and chooses an optimal level of oil exploitation. A group of kingmakers, on the other side, decides whether to stage a coup d'état and establish a new dictator. The relationship between oil endowment and the duration of the dictatorial regime is modulated by the price of oil. Applying an empirical survival model on data for the duration of 106 dictatorships supports the predictions of the theoretical model.
Keywords: Q34; D72; H11; 330; natural resources; dictatorship; political economy; duration; Erdölvorkommen; Diktatur; Dauer; Public Choice; Welt